A detailed investigation on the performance, combustion, and exhaust emission characteristics of a diesel engine running on the blend of diesel fuel, biodiesel and 1-heptanol (C7 alcohol) as a next-generation higher alcohol. (1st September 2020) - Yesilyurt, Murat Kadir
Graphical abstract: Highlights: 1-heptanol is used with peanut oil biodiesel/diesel fuel blend in the diesel engine. 1-heptanol and biodiesel concentration is kept constant as 20% on a volume basis. 1-heptanol due to its better fuel properties improves the engine characteristics. Combustion behavior improved with 1-heptanol use, relating to its oxygen content. 1-heptanol can be taken into account as a promising oxygenated fuel additive. Abstract: Alcohols are exceptional alternative fuels for the utilization in the compression-ignition (CI) engine due to their built-in fuel improving characteristics such as higher calorific value, higher cetane number, etc. Contrary to the lower-chain alcohols (methanol-C1, ethanol-C2, and propanol-C3), higher alcohols have an encouraging candidate for future diesel engine applications. Among the higher alcohols, 1-heptanol, having seven carbon atoms in the chemical structure, has preferable fuel properties. Therefore, there is a need to perform it as well as its blends with diesel fuel and biodiesel in the CI engine for extracting the characteristics of performance, emissions, and combustion. The objective of the present research work was to investigate the engine performance, exhaust gas emissions, and combustion behavior of a single-cylinder, four-stroke, water-cooled, naturally-aspirated, direct-injection (DI) diesel engine running on the binary blends of 1-heptanol/diesel fuel and biodiesel/diesel fuel, and finally the ternary type of their derivations of 1-heptanol/biodiesel/diesel fuel. For the experimental usage, the biodiesel fuel was synthesized from the peanut oil through the transesterification process in the presence of potassium hydroxide and methanol. The several tested fuel samples were prepared by splash blending technique as B20 (20% peanut oil biodiesel and 80% diesel fuel), Hp20 (20% 1-heptanol and 80% diesel fuel), B20Hp20 (20% peanut oil biodiesel, 20% 1-heptanol and 60% diesel fuel). To acquire the engine characteristics, the engine tests were carried out at four engine loads (25%, 50%, 75%, and 100%) with a fixed engine speed of 1500 rpm. The experimental outcomes revealed that the least brake specific energy consumptions for diesel fuel, B20, Hp20, B20Hp20, and B100 were found to be at 8.78 MJ/kWh, 8.90 MJ/kWh, 8.85 MJ/kWh, 8.94 MJ/kWh, and 10.29 MJ/kWh, respectively at 100% load while the maximum brake thermal efficiency values were obtained as 40.81%, 40.46%, 40.67%, 40.27%, and 35.00, respectively. At 100% load, the peak heat release rate for B20, Hp20 and B20Hp20 were found to be at 37.53 J/deg, 37.80 J/deg and 37.91 J/deg, respectively while diesel fuel and peanut oil biodiesel have in order of 40.22 J/deg and 27.66 J/deg. The addition of 1-heptanol as an oxygenated additive into the diesel fuel and biodiesel/diesel fuel blend caused to decreasing CO and unburned HC emissions while increasing CO2, O2, and NOX emissions as compared to diesel fuel. It can be concluded that this paper discusses the viability of suggesting biodiesel-diesel-alcohol blends to supply the future energy demands of the world.